Evaluation of different methods of laparoscopic treatment of common bile duct stones - Elghamry, Elghamry E.; Elsheikh, Mohamed M.; Mohamed, Hamdy A. (International Surgery Journal, 2019)
Background: Common bile duct (CBD) stones are the second most common complication of gall bladder stones. The best management of patients with CBD stones remains controversial. The aim of this study was to evaluate the methods of laparoscopic CBD exploration (LCBDE). Methods: This prospective study was conducted on 30 patients with CBD stones through 2 years. CBD stricture was excluded. Authors used transcystic and transcholedochotomy approaches for LCBDE either with or without choledoschope. Primary repair of the choledochotomy incision was done. Results: The mean age was 48.90±11.84 years. Biliary colic was the presentation in 63.3% of patients. The transcystic approach for CBD exploration was used in 16 cases without conversion, 11 cases were completed without choledochoscope, while 5 cases with choledochoscopic guided extraction. Choledochotomy approach had been used in 13 cases, 6 cases were completed with choledochoscope and 7 cases without it, two cases of them failed. One case failed from the beginning and was converted to open exploration. 5 ERCP previously inserted stents were removed. The mean operative time was 162.33±74.67 min. Bile leakage occurred in 2 cases following the choledochotomy approach. The mean hospital stay was 3.37±1.38 days. Conclusion: LCBDE is a feasible, effective and safe approach to bile duct stones. Depending on proper training and gaining experience.